RECENT DEVELOPMENT OF RADIONUCLIDE-BASED IMAGING IN DIAGNOSIS AND THERAPY OF LUNG CANCER: A REVIEW - HOLIK, HOLIS ABDUL; ARISTAWIDYA, LEVINA (International Journal of Applied Pharmaceutics, 2022)
This review was conducted to review the recent development of radionuclides that potentially used in diagnosis and therapy of lung cancer. A comprehensive article search used a systematic review method based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The article search was conducted using online databases, such as PubMed, ScienceDirect, and Google scholar with inclusion criteria: studies are related to lung cancer and radiopharmaceuticals, contained clinical research results, and were published in the last five years. Five articles were selected and they were analyzed and summarized. Three studies have reported the preclinic data and two studies have reported the clinical data of a phase I study. Two of five studies showed the nuclides were potentially used for NSCLC, one of five studies showed the nuclide was potentially used for SCLC, and the other two studies showed their nuclides were potentially used for both NSCLC and SCLC. 131I-Bevacizumab and 177Lu-Satoreotide Tetraxetan are potential for therapy lung cancer which showed the reduction of tumor uptake, while 89Zr-DFO-nimotuzumab, 68Ga-3PTATE-RGD, and 89Zr-DFOPODS-DAR2SC16-MB1 are potential for diagnosis because it showed high radioactivity concentrations in tumor-bearing mice. Based on five articles, the radionuclides in included articles have shown good results that indicate they are potential. However, some radionuclides still require further complement assessment research to improve their shortcomings.